Guest Editorial: N4A Appeal for Student Athletes to Study Abroad - Baron, Ken (My University, 2006)
The guest editorial encourages athletic advisors to provide study abroad opportunities for athletes to develop career maturity and have global exposure.
Keywords: editorial; study abroad; career development